Tissue plasminogen activator reduces the elevated intraocular pressure induced by prednisolone in sheep - Candia, Oscar A. (2014)
We have previously shown that tissue plasminogen activator (tPA) injected in the vitreous of sheep, reduced or prevented the elevation of the intraocular pressure (IOP) normally produced by the instillation of 1% prednisolone. We now report the effect of tPA when injected into the anterior chamber (AC) in amounts of 0.01, 0.001 and 0.0001 μg diluted in a volume of 50 μL. Lyophilized tPA, obtained as Actilyse 50 mg from Boehringer Ingelheim containing arginine was utilized. The Actilyse was diluted in balanced salt solution to obtain the desired amount of tPA in 50 μL. An identical solution containing only arginine was prepared to inject into the contralateral eye as a control. Six sheep of the Corriedale breed were selected. At the beginning of the study all eyes received instillation of 1% prednisolone 3 times/day for 10 days to elevate their IOP from 10 mm Hg to about 23 mm Hg. Then, 0.0001 μg was injected into one of the eyes and its effect was followed for up to 55:00 h while the instillation of prednisolone continued in both eyes. The same protocol was implemented for the 0.001 and 0.01 μg amounts after extended washout and IOP was over 22 mm Hg. The injection of 0.0001 μg into the AC had no effect on an IOP of 23.0 mm Hg at 6:00 and 30:00 h after injection. 0.001 μg of tPA reduced IOP from 23.1 to 18.6 mm Hg at 6:00 h but IOP recovered to 22.3 mm Hg at 30:00 h. Injection of 0.01 μg produced a marked and prolonged reduction of IOP. From a baseline of 23.0, IOP was reduced to 14.0, 14.7, 21.2, and 20.9 mm Hg at 5.0, 23.0, 27.0 and 45.5 h, respectively. The 0.423 μg of arginine, which is associated with 0.01 μg tPA, was injected alone and had no effect. Recombinant human tPA injected in the AC is effective in reversing steroid-induced IOP elevation in sheep. The reduction of IOP elevation may be the result of an effect on extra-cellular matrix turnover in the TM. These findings suggest that tPA may by useful as a therapeutic agent in steroid-induced glaucomas.